Entry Sites of Venezuelan and Western Equine Encephalitis Viruses in the Mouse Central Nervous System following Peripheral Infection - Phillips, Aaron T. (J Virol, 2016)
Venezuelan and western equine encephalitis viruses (VEEV and WEEV; Alphavirus; Togaviridae) are mosquito-borne pathogens causing central nervous system (CNS) disease in humans and equids. Adult CD-1 mice also develop CNS disease after infection with VEEV and WEEV. Adult CD-1 mice infected by the intranasal (i.n.) route, showed that VEEV and WEEV enter the brain through olfactory sensory neurons (OSNs). In this study, we injected the mouse footpad with recombinant WEEV (McMillan) or VEEV (subtype IC strain 3908) expressing firefly luciferase (fLUC) to simulate mosquito infection and examined alphavirus entry in the CNS. Luciferase expression served as a marker of infection detected as bioluminescence (BLM) by in vivo and ex vivo imaging. BLM imaging detected WEEV and VEEV at 12 h postinoculation (hpi) at the injection site (footpad) and as early as 72 hpi in the brain. BLM from WEEV.McM-fLUC and VEEV.3908-fLUC injections was initially detected in the brain's circumventricular organs (CVOs). No BLM activity was detected in the olfactory neuroepithelium or OSNs. Mice were also injected in the footpad with WEEV.McM expressing DsRed (Discosoma sp.) and imaged by confocal fluorescence microscopy. DsRed imaging supported our BLM findings by detecting WEEV in the CVOs prior to spreading along the neuronal axis to other brain regions. Taken together, these findings support our hypothesis that peripherally injected alphaviruses enter the CNS by hematogenous seeding of the CVOs followed by centripetal spread along the neuronal axis. IMPORTANCE VEEV and WEEV are mosquito-borne viruses causing sporadic epidemics in the Americas. Both viruses are associated with CNS disease in horses, humans, and mouse infection models. In this study, we injected VEEV or WEEV, engineered to express bioluminescent or fluorescent reporters (fLUC and DsRed, respectively), into the footpads of outbred CD-1 mice to simulate transmission by a mosquito. Reporter expression serves as detectable bioluminescent and fluorescent markers of VEEV and WEEV replication and infection. Bioluminescence imaging, histological examination, and confocal fluorescence microscopy were used to identify early entry sites of these alphaviruses in the CNS. We observed that specific areas of the brain (circumventricular organs [CVOs]) consistently showed the earliest signs of infection with VEEV and WEEV. Histological examination supported VEEV and WEEV entering the brain of mice at specific sites where the blood-brain barrier is naturally absent.